2002
DOI: 10.1034/j.1399-3054.2002.1140301.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the driving forces for water lifting in the xylem conduit?

Abstract: After Renner had shown convincingly in 1925 that the transpirational water loss generates tensions larger than 0.1 MPa (i.e. negative pressures) in the xylem of cut leafy twigs the Cohesion Theory proposed by Böhm, Askenasy, Dixon and Joly at the end of the 19th century was immediately accepted by plant physiologists. Introduction of the pressure chamber technique by Scholander et al. in 1965 enforced the general belief that tension is the only driving force for water lifting although substantial criticism reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 61 publications
(160 reference statements)
1
22
0
Order By: Relevance
“…This could be verified by measurements using the minimal-invasive microcapillary cell turgor and xylem pressure probes * Note that pressure probes mounted in a non-contact mode close to the leaf surface showed no P p changes indicating that they resulted from effects of temperature on stomata and in turn, on turgor pressure. (Zimmermann et al 2002(Zimmermann et al , 2004. As indicated in Figure 4 the ZIM-probes provide the same information as the highly sophisticated microcapillary probes, but with the important difference that measurements can be performed in the field .…”
Section: Effects Of Stomata Aperture Oscillations On Turgor Pressurementioning
confidence: 87%
“…This could be verified by measurements using the minimal-invasive microcapillary cell turgor and xylem pressure probes * Note that pressure probes mounted in a non-contact mode close to the leaf surface showed no P p changes indicating that they resulted from effects of temperature on stomata and in turn, on turgor pressure. (Zimmermann et al 2002(Zimmermann et al , 2004. As indicated in Figure 4 the ZIM-probes provide the same information as the highly sophisticated microcapillary probes, but with the important difference that measurements can be performed in the field .…”
Section: Effects Of Stomata Aperture Oscillations On Turgor Pressurementioning
confidence: 87%
“…following addition of 20 mM NaCl, which shows the importance of ions in the formation of gels (cited in Zimmermann et al, 2002a).…”
Section: Tablementioning
confidence: 97%
“…8c). Stomata closure prevents water loss [60], leading to decreased CO 2 concentration inside the leaf. Lee et al [61] demonstrated that pathogen-infected guard [62].…”
Section: Fig 7 Herementioning
confidence: 99%